Role of the CAG Repeat Polymorphism of the Androgen Receptor Gene in Polycystic Ovary Syndrome (PCOS) - Schüring, A. N.; Welp, A.; Gromoll, J.; Zitzmann, M.; Sonntag, B.; Nieschlag, E.; Greb, R. R.; Kiesel, L. (Experimental and Clinical Endocrinology & Diabetes, 2012)
Polycystic ovary syndrome (PCOS) is a frequent heterogenic disorder with a familial background. Androgenic effects, determining the clinical features of the syndrome, are mediated by the androgen receptor (AR), whose activity is modulated by a genetic polymorphism. We investigated the role of the CAG repeat polymorphism of the androgen receptor in PCOS.In the infertility unit of a university clinic, 72 PCOS patients were compared with 179 ovulatory controls undergoing a standardized diagnostic work-up. The number of CAG repeats was determined by PCR, labelling with IR-800 and PAGE. X-chromosome inactivation was assessed by a methylation-sensitive assay.Compared to controls, PCOS patients displayed a shorter mean CAG repeat length, encoding for higher AR activity (P=0.001). CAG repeat length correlated inversely with oligomenorrhea, a central androgen dependent feature of the syndrome (P=0.005). In a binomial regression analysis including BMI, LH and free testosterone, CAG repeat length was identified as an independent risk factor for PCOS (P=0.002).The CAG repeat polymorphism could constitute one of the genetic factors modulating the syndrome’s phenotype, contributing to its clinical heterogeneity and associated metabolic consequences.
Keywords: polycystic ovary syndrome; hyperandrogenemia; luteinizing hormone; androgen receptor; genetic polymorphism